Thermal decomposition of potassium titanium oxalate - KARUVANTHODI MURALEEDHARAN; LABEEB PASHA (Journal of the Serbian Chemical Society, 2011)
The thermal decomposition of potassium titanium oxalate (PTO) was studied using non-isothermal thermogravimetry at different heating rates under a nitrogen atmosphere. The thermal decomposition of PTO proceeds mainly through five stages forming potassium titanate. The theoretical and experimental mass loss data are in good agreement for all stages of the thermal decomposition of PTO. The third thermal decomposition stage of PTO, the combined elimination of carbon monoxide and carbon dioxide, were subjected to kinetic analyses both by the method of model fitting and by the model free approach, which is based on the isoconversional principle. The model free analyses showed that the combined elimination of carbon monoxide and carbon dioxide and formation of final titanate in the thermal decomposition of PTO proceeds through a single step with an activation energy value of about 315 kJ mol-1.